Detecting inhomogeneity of rainfall series in Peninsular Malaysia - Suhaila, Jamaludin; Deni, Sayang Mohd; Jemain , Abdul Aziz (2008)
The daily rainfall series from 50 stations in Peninsular Malaysia for the period 1975 to 2004 were tested for inhomogeneity. Four homogeileity tests were the Standard normal homogeneity test, Buishand range test, Pettitt test, and von Neumann ratio test. This study considered two aspects; the choices of the threshold values and the testing variables. First, two threshold values i.e. 0. 1 mm and 1 mm were compared. Second, two testing variables namely, annual rainfall amount and annual number of wet days, were evaluated. The results of homogeneity tests indicate that there are-almost no differences between both threshold values when the annual amount series and annual wet day series are used as the testing variables. Based on amount series, only 10% of the station series are detected as inhomogeneous series. Meanwhile 86% are considered as homogeneous and are useful for trend and variability analyses. In the case of wet day series, 72% of the station series are homogeneous while 14% are considered suspect. Results from the trend analysis showed that almost all inhomogeneous. stations displayed significant trends and the break in the series indicated the beginning year of the trend.